A nostalgic look back at library hi tech(nology). Issue 1 (20th March 2017) - Matthews, Joe
Abstract : Purpose: The purpose of this paper is to reflect on the history of information technology and computers in libraries over the last 50 years. Design/methodology/approach: This paper represents a personal perspective and reflects the views and opinions of the author. It is not intended to be an authoritative reporting of this history. Findings: This paper suggests that libraries were generally too shortsighted in their application of information technology and computing and submits that there are significant challenges facing libraries today. Research limitations/implications: No research was conducted. Practical implications: The author identifies several issues that libraries must confront in order that the automated systems being implemented add value for staff members but most importantly for users of library systems and services. Social implications: The paper suggests that libraries are facing a number of challenges based on a historical review of how libraries have adopted and adapted to information technology over the past 50 years. Originality/value: This paper, due to its personal perspective, reflects an original viewpoint.